Isu Pengkategorian Hadis Sebagai Ẓan Menurut Perspektif Qiyās Al-Shabah: The Issue of Categorization of Hadith as Ẓan According to Qiyās al-Shabah Perspective - Nik Mohd Rosdi, NIk Mohd Sofa’Urrahman; Ali, Abdul Karim; Syed Jaafar, Syed Mohd Jeffri (Jurnal Fiqh, 2022)
Khilafiah issues in Malaysia have become polemics that give a negative impression to the community. The purpose of this writing is to highlight the Qiyas al-Shabah instrument in identifying the qiyas method used on issues arising among Islamic scholars in Malaysia. The difference in views of Islamic scholars is usually because of an individual’s propensity towards certain manhaj. The difference in manhaj significantly impacts the Qiyas al-Shabah which consequently be used in eliciting the nas of the Qur’an and al-Sunnah, as well as the words of the imams of the madhhab. Hence, Qiyas al-Shabah is one of the methods of ‘illah in Fiqh and understanding it leads to openness and tolerance. This research is a qualitative study which will use a reference approach that involves theoretical and practical analysis.